Paradise Lost? : Growth, Convergence and Migration in the South Pacific - Loayza, Norman (IMF Working Papers; Working Paper ;, 1995)
This paper examines the determinants of growth for nine South Pacific countries during the period 1971-93, using the analytical framework of the Solow-Swan neoclassical growth model. Chamberlain's II-matrix estimator is used to account for unobserved country-specific heterogeneity in the growth process, and to control for errors-in-variables bias in calculations of real per-capita GDP. The speed of convergence of South Pacific countries to their respective steady-state levels of per-capita GDP, after controlling for the important regional effects of net international migration, is estimated at a relatively fast 4 percent per year. In addition, private and official transfers emanating from regional donor countries have kept the dispersion of real per-capita national disposable income constant over the period, despite a significant widening in the regional dispersion of real per-capita GDP.